Rocket Velocity Estimation for RX-450 Launches Using Image Processing - Junjunan, Soleh Fajar; Nugroho, Yuniarto Wimbo; Jihad, Bagus Hayatul (National Institute of Aeronautics and Space - LAPAN, 2022)
The RX-450 rocket, developed by the Rocket Technology Center BRIN, serves various purposes, from sounding to military applications. This study focuses on estimating rocket velocity during the launch phase. Using MATLAB for image processing and OpenRocket for simulation, we explore the potential of image processing for velocity estimation, providing a cost-effective alternative. Results show velocity estimations trailing those of OpenRocket, attributed to friction force and setup differences. The study emphasizes the importance of camera positioning for accuracy. Despite differences, image processing shows promise, warranting further refinement